Field report: mitigating ammonia emissions using a novel atomizing air cleansing technology - James McNaughton; Wendy Attuquayefio; Michael Roberts (Journal of Applied Poultry Research)
SUMMARY: Ammonia (NH₃) odor influences growth performance and harms broilers at market age. The Atomizing Vapor Particles Air Cleansing Technology atomizes liquid into small droplets, to maximize surface area for the removal of NH₃, and can be used as an effective agricultural waste and industrial air purification system to prevent anorexia in broilers. The objectives of this research were to (1) introduce atomization as a cost-effective method for reducing NH₃ emissions, (2) evaluate NH₃ concentrations in the brooding house following atomization and acidified litter amendment treatments, targeting levels below 15 parts per million (ppm). Trial 1 evaluated the efficacy of 8 NH₃ control strategies, comparing different litter types (fresh vs. >4-year-old), litter control (atomization, citric acid with/without water, acidified litter amendment), and ventilation schedules (0-14 days no ventilation, then 30‑sec every 5 min from 15 to 48 days vs. continuous ventilation 30‑sec every 5 min from 0 to 48 days). Target NH₃ levels ranged from <15 to <35 ppm across treatments. In trial 2, eight NH₃ control strategies in combination with different NH₃ stress levels were tested. This included a clean, zero-stress, no-litter amendment control (T1), atomized vapor air NH₃ control (T2-T4), acidified litter amendments using sodium bisulfate to control for NH₃ (T5-T7), and no NH₃ control strategy on old litter. Treatment 6 represents the 2024 industry standard, which uses aggressive ventilation with sodium bisulfate litter treatment. Treatments also varied in strategies, ranging from continuous aggressive ventilation to no intervention in mild to extreme stress environments. The 1X atomization treatment of >5-year-old litter (T2) in the second trial kept NH₃ levels below 10 ppm. Combined, these findings revealed the importance of atomization in keeping NH₃ concentration low. Atomization in combination with ventilation strategies might help to optimize broiler growth while minimizing environmental stress and the negative effects of odor and anorexia on broiler chickens.